Dampak Pandemi COVID-19 Pada Kesehatan Mental Wanita Hamil: Tinjauan Literatur - Vini Yuliani; Husnul Khatimah; Yunita Laila Astuti (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The COVID-19 pandemic is still a concern for the world community, especially pregnant women who are very vulnerable to COVID-19 disease. During pregnancy, there is an increase in psychological problems and this condition can be exacerbated by the COVID-19 pandemic which requires the implementation of social distancing. This can increase anxiety in pregnant women, making them more susceptible to perinatal depression. This study aimed to analyze psychological health problems during the COVID-19 pandemic and the impact on pregnant women. The method used was a literature review using online databases including PubMed, Wiley, Springer, Taylor & Francis, and Science Direct. Selected articles based on criteria namely full text, open access, in English, and published in 2021. Ineligible articles were eliminated after being screened by title, abstract, and overall text. The number of eligible articles was six articles. The literature review results showed that pregnant women during the COVID-19 pandemic tend to experience increased anxiety, emotion, depression, stress, insomnia, or post-traumatic stress disorder. Mental health disorders during pregnancy have a negative impact on mothers, babies, and their families, because they increase the risk of abortion, premature birth, and mental disorders in babies born. An approach that can be taken to prevent psychological problems in pregnant women is to implement quality antenatal care, especially screening or psychological assessments for pregnant women so the problems related to mental health in pregnant women can be addressed immediately.